INFORMASI AKUNTANSI DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA UMKM KASUR IBU NUNUNG DI CIKAMPEK - Nuramaliah, Puput; Nur Supiyanti, Salsa; Lina Situngkir, Tiar (Pusat Riset dan Inovasi Nasional, 2022)
This study has the aim of understanding and knowing how to calculate the cost of goods manufactured using the process costing method in Mrs. Nunung's mattress business in the Karawang district. The method used in this research is a case study with direct field observations and interviews with the business owner, Mrs. Nunung. The results of the research that have been carried out show that the production costs incurred for the September 2021 period amounted to IDR 62,3766,000 consisting of raw material costs IDR 55,016,000, auxiliary material costs IDR 2,180,000, labor costs IDR 4,680,000, and factory overhead costs IDR 500,000. The production cost added to each unit of mattress is IDR 121,061. So that there is a difference in calculations between the calculations of researchers and calculations according to Nunung's mother of IDR 3,939. The total income of Mrs. Nunung's Mattress Business in September 2021 is IDR 78,000,000.